Indigenous practices of ecosystem management in a changing climate: Prospects for ecosystem-based adaptation. Issue 126 (December 2021) - Chanza, Nelson; Musakwa, Walter
Abstract: Based on data on experienced ecosystem services of selected rural communities in Zimbabwe, this research adopts the millennium ecosystem assessment (MEA) and nature's contribution to people (NCP) frameworks to understand the role of indigenous knowledge systems (IKS) in managing ecosystems and its potential in enhancing climate change responses. The study was motivated by the limited understanding about how indigenous communities are using ecosystems to adapt to climate change. A qualitative research paradigm involving focus group interactions with purposively selected respondents informed the case study. Results show that indigenous practices have significant conservation potential. The motivation behind ecosystem management stems from recognition of diverse ecosystem services, which exist as: provisioning; regulatory and supporting; and spiritual and informative benefits. The participants attribute the perpetuation of these diverse benefits to keeping strong ties with their ancestors, a system that requires them to maintain their traditional ecosystem conservation practices, which has fairly withstood exogenous pressures of colonial and post-colonial legacies in Zimbabwe. Many of these practices exist as local ways of adapting to climate change through ecosystem-based practices. Indigenous communities have a collective obligation to protect ecosystems, which are inhabited by the spirits, whom they believe have powers to influence the local climate system. These observations reverberate the critical role of indigenous communities in ecosystem management and shed more insights to the design of ecosystem-based adaptation (EbA) interventions in communities endowed with rich indigenous forests and biodiversity. Highlights: MEA and NCP frameworks can determine broad ecosystems services from indigenous communities. Ecosystem conservation by indigenous people is motivated by spiritual connections. Indigenous governance structure facilitates local-based climate change responses. There are high prospects for supporting EbA in well governed indigenous communities.